2012
DOI: 10.1002/ccd.23389
|View full text |Cite
|
Sign up to set email alerts
|

Association of coronary lipid core plaque with intrastent thrombus formation

Abstract: Stenting of large LCPs may be associated with intrastent thrombus formation, suggesting that more intensive anticoagulant and/or antiplatelet therapy may be beneficial in such lesions. © 2012 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…As an example, coronary plaque composition can have an impact on the outcome of percutaneous coronary interventions (PCI). Stents overlying a lipidic core have been associated with long-term adverse healing responses within the stent [5,15,48,49], while stents implanted over a severely calcified region tend to have a higher risk of underexpansion, associated with higher risk of stent failure (e.g. stent thrombosis and in-stent restenosis) [50].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, coronary plaque composition can have an impact on the outcome of percutaneous coronary interventions (PCI). Stents overlying a lipidic core have been associated with long-term adverse healing responses within the stent [5,15,48,49], while stents implanted over a severely calcified region tend to have a higher risk of underexpansion, associated with higher risk of stent failure (e.g. stent thrombosis and in-stent restenosis) [50].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that periprocedural MIs are associated with increased atherosclerotic burden and large LCPs [115][116][117][118]. Indeed, embolization of the lipid core after stent implantation in a plaque with high lipid content has been identified as an important cause of periprocedural no-reflow and MI with and without the presence of intracoronary thrombus [118][119][120]. A pilot study performed in nine patients using an embolic protection device showed that embolized material consisted in fibrin and platelet aggregates, which reflects the highly thrombogenic content of necrotic core of large atheroma plaques and LCP [98,120,121].…”
Section: Prevention Of Periprocedural Complicationsmentioning
confidence: 99%
“…Indeed, embolization of the lipid core after stent implantation in a plaque with high lipid content has been identified as an important cause of periprocedural no-reflow and MI with and without the presence of intracoronary thrombus [118][119][120]. A pilot study performed in nine patients using an embolic protection device showed that embolized material consisted in fibrin and platelet aggregates, which reflects the highly thrombogenic content of necrotic core of large atheroma plaques and LCP [98,120,121]. In a sub-study of the COLOR (Chemometric Observation of Lipid-Core Plaques of Interest in Native Coronary Arteries) registry, a prospective multicenter observational study aiming to determine a relationship between NIRS-defined high LCBI and periprocedural MI, Goldstein et al [20] analyzed the cardiac biomarkers of 62 stable patients undergoing PCI.…”
Section: Prevention Of Periprocedural Complicationsmentioning
confidence: 99%
“…et .al [23]201269To compare the target lesion length using NIRS combined with angiography vs. angiography alonePatients undergoing stent implantation could have LCP extending beyond the intended treatment margins as defined using QCA alone Am J Cardiol Brugaletta, S. et .al [27]2012202To explore a relationship between lipid plaque composition by NIRS and angiographic severity of coronary artery diseasePatients with highest Syntax score have a higher LCBI JACC Cardiovasc Imaging Brilakis, E.S. et .al [16]20129To investigate whether use of an embolic protection device might prevent complications of LCP interventionsUse of embolic protection devices frequently resulted in embolized material retrieval after stenting of native coronary artery lesions with large LCP Catheter Cardiovasc Interv Brugaletta, S. et .al [28]201268To assess LCP distribution in nonculprit coronary arteries using NIRSLCP were mainly located in proximal portions of the LAD and LCX, and more uniformly distributed in the RCA; JACC Cardiovasc Imaging Kini, A.S. et .al [15]201387To determine the impact of short-term intensive statine treatment on intracoronary plaque lipid contentShort-term intensive treatment with statine may reduce lipid content in obstructive coronary lesions JACC Papayannis, A.C. et .al [24]20139To examine the association between presenting LCP (by NIRS) and poststenting thrombus formation (by OCT)Stenting large LCPs may be associated with intrastent thrombus formation Catheter Cardiovasc Interv Townsend, J.C. et .al [29]2013100To investigate, whether coronary bifurcations have higher levels of intracoronary LCP than non-bifurcation regionsCoronary bifurcations do not appear to have higher levels of intracoronary LCP than their comparative non-bifurcation regions Am J Cardiol Maini, A. et .al [30]201377To evaluate LCP modification with coronary revascularization and its correlation with periprocedural MIPlaque modification may be performed successfully using interventional methods and can be evaluated with NIRS; axial plaque shifting is an acute prognostic marker for postprocedure MI J Inv Cardiol Madder, R.D. et .al [31]…”
Section: Experience Using Nirs For Coronary Plaque Imaging In Humans mentioning
confidence: 99%